PERAN PENALARAN MORAL DALAM PENDIDIKAN AKHLAQ MULIA - Safrilsyah Safrilsyah; Mohd Zailani bin Mohd. Yusoff; Mohamad Khairi bin Othman (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2017)
Islam is a religion that is very concerned with noble morality. So the main focus of sending the Messenger of Allah to the face of the earth is to perfect human morality. In the view of Islam, a Muslim who has a noble morality will gain happiness in himself and benefit the surrounding community. Among the benefits of noble morality is to strengthen and perfect the religion, facilitate the calculation of charity in the afterlife, eliminating the difficulties of life and survival in the world and the hereafter. One effort to form akhlaqul karimah on learners needed akhlaq education with moral psychology approach. Akhlaq education with psychological approach is an alternative process of guidance and teaching akhlaq to learners with emphasis on moral reasoning, it will manifest students who are able to distinguish the noble akhlaq and akhlaq disgraceful. With moral reasoning is expected learners have the motivation and able to consider the actions taken to be implemented in accordance with the moral values prevailing in society and also has noble morals in accordance with Islamic teachings. Students are able to act intelligently with good deeds and piety.